IMMU-18. TARGETING H3.3 K27M MUTATION AS A SHARED NEOANTIGEN IN HLA-A*0201+ PATIENTS WITH DIFFUSE MIDLINE GLIOMAS – DEVELOPMENT OF A NOVEL MASS CYTOMETRY-BASED MONITORING OF VACCINE-REACTIVE, EPITOPE-SPECIFIC CD8+ T CELL RESPONSES. (23rd April 2019) - Taitt, Jared; Watchmaker, Payal; Almeida, Neil; Okada, Kaori; Shahin, Maryam; Mueller, Sabine; Okada, Hideho
Abstract: Diffuse midline glioma (DMG), including diffuse intrinsic pontine glioma (DIPG) constitutes up to 20% of pediatric brain cancer and has a median survival of less than one year. The ongoing development of immunotherapy has shown significant promise in many fields, including that of gliomas. Genetic studies have revealed that greater than 70% of DIPG cases harbor an amino acid substitution from lysine (K) to methionine (M) at position 27 of histone 3 variant 3 (H3.3). We have previously identified novel HLA-A*02:01-restricted neoantigen epitope encompassing the H3.3K27M mutation. Accordingly, we have implemented a clinical trial through the Pacific Pediatric Neuro-Oncology Consortium (PNOC). Newly diagnosed DIPG patients who are HLA-A2+ and H3.3K27M+ underwent radiation therapy, and then received the H3.3K27M peptide vaccine, combined with the tetanus toxoid (TT) peptide, emulsified in Montanide. The TLR3 agonist, Poly-ICLC, was given concurrently to improve therapeutic effects of the vaccine. Our objective is to characterize vaccine-induced H3.3K27M-specific T cells from peripheral blood at several time points of the study through the evaluation of a large number of analytes utilizing a novel H3.3K27M-specific dextramer-based mass cytometry method. The specificity of the H3.3K27M-specific dextramer was validated through significant binding to H3.3K27M TCR-transduced CD8 T cells and lack of non-specific binding. Subsequently, patient-derived PBMC samples were analyzed using this methodology, revealing a time course-dependent, progressive expansion of CD45RA+ effector memory cells with an inverse downregulation of CD45RO+ in H3.3K27M-specific CD8 T cells. Additionally, progressive upregulation of HLA-DR was observed in several myeloid-derived populations through the course of the trial. Future plans include the longitudinal quantification of IFN-γ and TNF-α expression as a response to the H3.3K27M peptide vaccine at each time point. The development of this methodology may greatly aid in the comprehensive evaluation of immunotherapeutic outcomes on the cellular basis.